2013
DOI: 10.1111/sum.12066
|View full text |Cite
|
Sign up to set email alerts
|

The development of a methodology using fuzzy logic to assess the performance of cropping systems based on a case study of maize in the Po Valley

Abstract: The development of tools for evaluating the sustainability of cropping systems is fundamental to providing reliable information on crop performance. In this study, an integrated index [Performance Index (PI)] was developed based on environmental, production and cost variables. In this approach, data are aggregated using a fuzzy logic-based procedure to deal with the inherent subjectivity at each aggregation step. The PI was tested for three cropping systems in the Po Valley (northern Italy) where maize was gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…According to Zhang [13], the fuzzy model obtained the most accurate results in the determination of phosphorus uptake by plants. In the same way, Carozzi et al [71] determined the performance of cropping systems, using corn as case study, and found lower error using fuzzy modeling in comparison to regression analysis. Applications with fuzzy modeling in agriculture have shown results with greater precision, as in the energy savings in a rotary dryer calculated with a fuzzy multivariable control application, which reduced biomass consumption by 9% [72].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Zhang [13], the fuzzy model obtained the most accurate results in the determination of phosphorus uptake by plants. In the same way, Carozzi et al [71] determined the performance of cropping systems, using corn as case study, and found lower error using fuzzy modeling in comparison to regression analysis. Applications with fuzzy modeling in agriculture have shown results with greater precision, as in the energy savings in a rotary dryer calculated with a fuzzy multivariable control application, which reduced biomass consumption by 9% [72].…”
Section: Discussionmentioning
confidence: 95%
“…Carozzi et al [71] used the fuzzy model for the determination of corn response producing and found that the least error occurred when compared with regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A new evaluation-interpretation cycle can be run any time that new versions (solutions) of the modeling system are developed. Again, a well-designed, component-based evaluation system can be easily extended toward including further evaluation approaches to keep up with evolving methodologies, i.e., statistical or fuzzy-based (e.g., Carozzi et al 2013;Fila et al 2014).…”
Section: Coupling Between Simulation and Evaluationmentioning
confidence: 99%